The pricing of audit services: evidence from the Kuala Lumpur Stock Exchange (KLSE) listed companies - Che Ahmad, Ayoib; Derashid, Chek (Universiti Utara Malaysia, 1996)
In practice, audit fees are determined based on agreement, negotiation and consensus between auditee and auditor. With the exception of the Malaysian Institute of Accountants' schedule for determining minimum audit fees, no specific guideline has been issued either by the Malaysian government or other accounting bodies. This study examined the explanatory power of previously identified factors that could influence the pricing of audit services in the Malaysian setting. The factors examined included the size of company (measured either by total assets or turnover), complexity of company (measured by the number of the companies in the same group, i.e., holding, as well as subsidiaries), profitability, liquidity and leverage of auditees, audit opinion, size and location of the auditors, audit season, audit delay, and classification of the industries in which the auditees operate. Consistent with previous studies, the size and complexity of the audited companies were found to be the major determinants of audit fees.